Hypokalemia associated with pseudo-Cushing’s syndrome and magnesium deficiency induced by chronic alcohol abuse - Kurajoh, Masafumi (CEN Case Rep, 2018)
Hypokalemia and hypomagnesemia are frequently observed in patients with chronic alcoholism. However, the involvement of deranged cortisol regulation in patients with those conditions has not been reported. A 63-year-old Japanese male with chronic alcoholism was referred to the Department of Diabetes, Endocrinology and Metabolism for examination and treatment of hypokalemic periodic paralysis. Laboratory findings showed hypokalemia (2.3 mmol/l), as well as a high level of urinary excretion of potassium and hypomagnesemia (1.2 mg/dl), whereas urinary excretion of magnesium was undetectable. Potassium infusion treatment recovered that level in serum to 4.1 mmol/l, though it decreased to 2.2 mmol/l following discontinuation. A dexamethasone suppression test and urinary cortisol level showed corticotropin-dependent hypercortisolemia. However, gadolinium-enhanced MRI revealed no evidence of pituitary adenoma. The patient recovered from hypokalemia following an administration of magnesium in addition to potassium, which was accompanied by potassium over-excretion improvement. After being discharged, serum potassium level was maintained within a normal range with only magnesium infusion treatment. Furthermore, alcohol intake was reduced from 160 to 20 g/day and an endocrinological re-examination after that restriction showed normal cortisol regulation. The patient was diagnosed with pseudo-Cushing’s syndrome induced by alcohol abuse. Serum potassium level was maintained within a normal range even after discontinuation of magnesium supplementation. Our findings in this case indicate that pseudo-Cushing’s syndrome in conjunction with hypomagnesemia may be involved in development of hypokalemia in patients with chronic alcoholism.